Gastric tonometry in septic shock. Issue 2 (1st February 1998) - Hatherill, M; Tibby, S M; Evans, R; Murdoch, I A
Abstract : OBJECTIVES: To investigate the prognostic value of intramucosal pH (pHi) and the relation among pHi, arterial pH, base excess, and lactate in children with septic shock. DESIGN: Children admitted to the paediatric intensive care unit with a diagnosis of septic shock were prospectively enrolled. A gastrointestinal tonometer (Tonometrics Division, Instrumentarium Corporation, Helsinki, Finland) was placed into the stomach and intramucosal pH, arterial pH, base deficit, and lactate were measured on admission and six hours later. Sequential data were analysed on 24 patients (17 survivors, seven non-survivors), median age 46 months (range: 2.8–168 months). RESULTS: Median pHi on admission was 7.39 (interquartile range 7.36–7.51) in survivors compared with 7.2 (interquartile range 7.18–7.35) in non-survivors (p = 0.01). There was no significant difference in arterial pH, base excess, or lactate among survivors and non-survivors. Admission pHi < 7.32 predicted mortality with sensitivity (57%), specificity (94%), and positive predictive value (80%). Patients with admission pHi < 7.32 who failed to improve ⩾ 7.32 within six hours (n = 3) had 100% mortality. CONCLUSION: In children with septic shock the admission pHi is significantly lower in non-survivors. pHi is a better prognostic indicator of mortality than either standard acid-base values or lactate. pHi < 7.32 that does not improve within six hours is associated with a poor prognosis.